Analysis of Obstetric Near Miss Cases of Different Health Facilities of Electoral Constituency Two of Arghakhanchi District - Manandhar, S R; Manandhar, D S; Adhikari, D; Shrestha, J R; Rai, C; Rana, H; Paudel, M (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to identify and analyze obstetric near miss cases at health facilities of electoral constituency number 2 (EC 2) of Arghakhanchi district, Nepal. Methods: After receiving one day training on identifying obstetric near miss cases, health facility staff of EC 2 of Arghakhanchi district filled up WHO derived obstetric near miss forms for eight months duration. Causes of obstetric near miss cases were identified and analyzed in SPSS 16. Results: There were 31 obstetric near miss cases reported from different health facilities of EC 2 of Arghakhanchi. The commonest cause of obstetric near miss was Post-partum Hemorrhage (85%, n=26) followed by obstructed labor and ante partum hemorrhage (6%, n= 2) each. The leading cause of PPH was retained placenta/placental tissue in 55% cases (14) followed by atonic uterus (27%, n= 7). Two fifth of the mothers (39%, n=12) developed complication during labor. The most common complication developed after labor was hemorrhage. Conclusions: This study highlighted PPH as the most common serious obstetric problem in the health facilities and indicates the need for provision of blood transfusion at the health facility at least at Arghakhanchi. DOI: http://dx.doi.org/10.3126/njog.v9i2.11760